Liquid-phase synthesis method of oxychloride electrolyte material
The oxide electrolyte material is prepared through the hydraulic synthesis method, solving the problem of high energy consumption, time -consuming and impurities pollution in solid -phase legal preparation, and realizing efficient and uniform electrolyte materials.
Patent Information
- Application Number
- CN202411338705.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, the solid-phase preparation of oxyhalide electrolyte materials has problems such as high energy consumption, long time consumption and easy introduction of impurities.
The liquid -phase synthesis method is adopted to dissolve the lithium source and M sources (such as SC, Y, Al, etc.) in the solvents, and obtained oxide electrolyte materials through evaporation and thermal treatment.
Improving the energy consumption and time consumption of solid phase method, reducing the introduction of impurities, and prepared electrolyte materials with high consistency and high lithium ion conductivity.
Smart Images

Figure CN119381522A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrolyte material synthesis, and in particular to a liquid phase synthesis method of an oxychloride electrolyte material. Background Art
[0002] In recent years, new energy vehicles have developed rapidly, and the market share of lithium-ion battery vehicles has increased year by year. Consumers' expectations for their endurance and safety performance are also constantly increasing. The energy density of conventional liquid lithium-ion batteries has approached its limit, and there are intrinsic safety risks due to the use of organic solvents as electrolytes. The development of solid-state batteries is expected to solve these two problems. Solid electrolytes, as the core materials of solid-state batteries, can be roughly divided into several technical routes such as oxides, polymers, sulfides, and halides. Among them, halides have advantages such as wide electrochemical windows and high lithium ion migration numbers, and are currently a hot direction for solid-state electrolyte research. The preparation methods of the Li3InCl6 system halide electrolyte, which is currently studied more, can be roughly divided into solid-phase method and liquid-phase method. The solid-phase method generally mixes the metal chloride raw materials by mechanical ball milling, and uses the energy provided by high-speed ball milling impact to promote the formation of the target product; while the liquid-phase method generally uses the characteristics of the raw materials being soluble in water to mix them in a solution, and obtains the target product by heating, stirring, and evaporating the solvent.
[0003] More and more studies have found that by introducing oxygen into the halide system and expanding the space for lithium ion movement in its crystal lattice, its lithium ion conductivity can be further improved, while increasing its antioxidant properties, making it compatible with higher voltage positive electrode materials. Currently, the synthesis of oxyhalides mostly adopts the solid phase method, that is, the preparation of oxyhalide electrolytes by mixing solid raw materials by mechanical ball milling. In order to obtain products with uniform and stable performance, it often requires a long time of high-energy ball milling, and the wear of ball milling beads and ball milling jars will introduce impurities. For example, the prior art Chinese invention patent application CN118117156A discloses a method for preparing a new type of oxyhalide electrolyte. The general chemical formula of the electrolyte can be written as Li b M y Al a O3X b+3a+3y-6, and its structure is an amorphous-UCl3 composite structure. Its preparation method is to mix metal halides, inorganic lithium salts, aluminum chloride and inorganic metal oxides by mechanical ball milling under the protection of an inert atmosphere, and the product is subjected to a pressing treatment (optional) and then a heat treatment to obtain an oxyhalide electrolyte with high ionic conductivity. Since the mechanical ball milling method is used for the reaction, the contact area between the solid particles is limited, and the activity of the reactants is low. In order to obtain a uniform target product, a very high ball milling energy needs to be provided. In fact, the ball milling mixing time is often as long as 1 to 3 days, the amount of powder prepared at one time is limited, and it is difficult to avoid impurity contamination caused by the wear of the grinding balls and the ball mill jars during long-term grinding, which is less cost-effective for continuous production. Summary of the invention
[0004] The present application provides a liquid phase synthesis method for oxychloride electrolyte materials, which improves the problems of high energy consumption, long time consumption, and easy introduction of impurities in the solid phase method for preparing oxyhalide electrolyte materials.
[0005] The present application provides a liquid phase synthesis method of an oxychloride electrolyte material, the method comprising:
[0006] Dissolving the reaction raw materials in a solvent to carry out a chemical reaction to obtain a product solution;
[0007] Evaporating the product solution to obtain solid particles;
[0008] The solid particles are heat treated to obtain an oxychloride electrolyte material Li x MO y Cl z , wherein M includes at least one of Sc, Y, Al, Ti, Zr, Hf, V, Nb and Ta, 1≤x / y≤4, 1≤z / y≤8;
[0009] Wherein, the reaction raw materials include a lithium source and a M source, and the M source includes M chloride.
[0010] As an optional embodiment, the lithium source includes at least one of Li2O, LiOH and LiCl.
[0011] As an optional embodiment, the M source includes at least one of ScCl3, YCl3, AlCl3, TiCl4, ZrCl4, HfCl4, VCl5, NbCl5 and TaCl5.
[0012] As an optional embodiment, the solvent includes at least one of water, ethanol, isopropanol, methanol, n-butanol, acetone, methyl acetate, ethyl acetate, tetrachloroethylene, trichloroethylene and tetrahydrofuran.
[0013] As an optional implementation manner, the mass ratio of the reaction raw material to the first solvent is 1:(8-1000).
[0014] As an optional implementation manner, the evaporation temperature is 60° C. to 120° C.; the evaporation time is 4 h to 12 h.
[0015] As an optional implementation manner, the temperature of the heat treatment is 100° C. to 500° C.; and the time of the heat treatment is less than or equal to 20 hours.
[0016] As an optional embodiment, the method further comprises mixing the solution with a hydrochloric acid solution to inhibit the hydrolysis of the metal chloride.
[0017] As an optional implementation manner, the volume concentration of hydrochloric acid in the hydrochloric acid solution is 30% to 36%.
[0018] As an optional implementation manner, the mass of the hydrochloric acid solution added does not exceed 3% of the total mass of the reaction raw materials.
[0019] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0020] The method provided in the embodiment of the present application adopts chloride of M as M source and lithium source to form reaction raw materials, utilizes the property that most metal chlorides are soluble in water, configures the reaction raw materials into an aqueous solution to form a liquid phase synthesis system, and then subjecting the evaporated solid to appropriate heat treatment to prepare the oxychloride electrolyte material, thereby improving the problems of high energy consumption, long time consumption, and easy introduction of impurities in the solid phase method for preparing oxyhalide electrolyte materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0023] Figure 1 A flowchart of the method provided in the embodiment of the present application. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0025] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0026] Figure 1 A flow chart of the method provided in the embodiment of the present application is as follows: Figure 1 As shown, the embodiment of the present application also provides a liquid phase synthesis method of an oxychloride electrolyte material, the method comprising:
[0027] S1. The reaction raw materials are mixed with a solvent, and then reacted to obtain a solution; wherein the reaction raw materials include a lithium source and an M source, and the M source includes a chloride of M;
[0028] In some embodiments, the lithium source includes at least one of Li2O, LiOH and LiCl. The M source includes at least one of ScCl3, YCl3, AlCl3, TiCl4, ZrCl4, HfCl4, VCl5, NbCl5 and TaCl5.
[0029] In some embodiments, the solvent includes at least one of water, ethanol, isopropanol, methanol, n-butanol, acetone, methyl acetate, ethyl acetate, tetrachloroethylene, trichloroethylene, and tetrahydrofuran.
[0030] In some embodiments, the mass ratio of the reaction raw material to the first solvent is 1:(8-1000). Exemplarily, the mass ratio of the reaction raw material to the first solvent can be 1:8, 1:100, 1:200, 1:300, 1:400, 1:500, 1:600, 1:700, 1:800, 1:900 or 1:1000, etc., and can also be any value within the range of 1:(8-1000).
[0031] In some embodiments, the method further comprises mixing the solution with a hydrochloric acid solution to inhibit hydrolysis of the metal chloride.
[0032] Further, the volume concentration of hydrochloric acid in the hydrochloric acid solution is 30% to 36%. The added mass of the hydrochloric acid solution does not exceed 3% of the total mass of the reaction raw materials. Exemplarily, the volume concentration of hydrochloric acid in the hydrochloric acid solution can be 30%, 31%, 32%, 33%, 34%, 35% or 36%, etc., and it can also be any value within the range of 30% to 36%. The added mass of the hydrochloric acid solution can be 0.5%, 1%, 1.5%, 2%, 2.5% or 3% of the total mass of the reaction raw materials, etc., and it can also be any value within the range of not more than 3%.
[0033] S2. evaporating the solution to obtain solid particles;
[0034] In some embodiments, the evaporation temperature is 60°C to 120°C; the evaporation time is 4h to 12h. Exemplarily, the evaporation temperature can be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, etc., and it can also be any value in the range of 60°C to 120°C. The evaporation time can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, etc., and it can also be any value in the range of 4h to 12h.
[0035] S3. Heat treating the solid particles to obtain an oxychloride electrolyte material Li x MO y Cl z , wherein M includes at least one of Sc, Y, Al, Ti, Zr, Hf, V, Nb and Ta, 1≤x / y≤4, 1≤z / y≤8.
[0036] In some embodiments, the temperature of the heat treatment is 100°C to 500°C; the time of the heat treatment is 0h to 20h. Exemplarily, the temperature of the heat treatment can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 350°C, 400°C, 450°C or 500°C, etc., and it can also be any value within the range of 100°C to 500°C. The time of heat treatment can be 0h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, etc., and it can also be any value within the range of 0h to 20h.
[0037] Specifically, in this embodiment, the preparation process of the oxyhalide electrolyte material can be to configure one or more of the reactants Li2O, LiOH, LiCl, ScCl3, YCl3, AlCl3, TiCl4, ZrCl4, HfCl4, VCl5, NbCl5, and TaCl5 into a mixed solution according to the designed stoichiometric ratio under the protection of an inert gas atmosphere. The solvent can be one or more of water, ethanol, isopropanol, methanol, n-butanol, acetone, methyl acetate, ethyl acetate, tetrachloroethylene, trichloroethylene, and tetrahydrofuran, and there is no restriction on the type and mixing ratio of the solvent. The mass ratio of the total mass of the reactants to the solvent is 1:1000 to 1:8. A small amount of 30-36% hydrochloric acid aqueous solution can be added according to the situation to inhibit the hydrolysis of the metal chloride, and the mass of the added hydrochloric acid does not exceed 3% of the mass of the solid reactant. The solution is stirred for more than 30 minutes to mix evenly, and the stirring is continued and the temperature is increased to evaporate the solvent. The solvent evaporation temperature is 60°C to 120°C, and the time used for complete evaporation is usually 4 to 12 hours. The solid particles obtained after the solvent is completely removed are first ground in an agate mortar, and then heat-treated under vacuum or inert gas protection as needed, with the heat treatment temperature being 100°C to 500°C and the time being 0 to 20 hours, to obtain oxychloride solid electrolyte powder.
[0038] The method adopts chloride of M as an M source and a lithium source to form a reaction raw material, utilizes the property that most metal chlorides are soluble in water, configures the reaction raw materials into an aqueous solution to form a liquid phase synthesis system, and then subjecting the evaporated solid to appropriate heat treatment to prepare an oxychloride electrolyte material, thereby improving the problems of high energy consumption, long time consumption, and easy introduction of impurities in the solid phase method for preparing oxyhalide electrolyte materials.
[0039] The electrolyte powder synthesized by this liquid phase method has a small particle size and good uniformity, and the electrical properties such as lithium ion conductivity are highly consistent. The product conversion rate is high, and since only organic solvents are used in the production process in addition to the raw metal salt, it is not easy to introduce other impurities. This method is easy to operate, has low energy consumption in the production process, can effectively reduce costs, and is convenient for scale-up experiments and mass production, laying the foundation for the development of low-cost, high-energy-density, high-rate performance solid-state batteries.
[0040] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0041] Example 1
[0042] An oxyhalide electrolyte material, the preparation process of which is as follows:
[0043] In a glove box, weigh 0.8142g LiOH and 9.1858g NbCl5, mix with 200ml isopropanol in a beaker, and stir at room temperature until completely dissolved. Heat the solution to 80°C and continue stirring until the solution evaporates completely, leaving a gray solid at the bottom of the beaker. Scrape the solid from the bottom of the beaker, grind it in an agate mortar, and heat treat it in a muffle furnace at 120°C for 5h to obtain the oxyhalide electrolyte material LiNbOCl4 powder.
[0044] Example 2
[0045] An oxyhalide electrolyte material, the preparation process of which is as follows:
[0046] In a glove box, weigh 0.8142g LiOH and 9.1858g NbCl5, mix with 200ml isopropanol in a beaker, and stir at room temperature until completely dissolved. Heat the solution to 80°C and continue stirring until the solution evaporates completely, leaving a gray solid at the bottom of the beaker. Scrape the solid from the bottom of the beaker, grind it in an agate mortar, and heat treat it in a muffle furnace at 150°C for 5h to obtain the oxyhalide electrolyte material LiNbOCl4 powder.
[0047] Example 3
[0048] An oxyhalide electrolyte material, the preparation process of which is as follows:
[0049] In a glove box, weigh 0.8142g LiOH and 9.1858g NbCl5, mix with 200ml isopropanol in a beaker, and stir at room temperature until completely dissolved. Heat the solution to 80°C and continue stirring until the solution evaporates completely, leaving a gray solid at the bottom of the beaker. Scrape the solid from the bottom of the beaker, grind it in an agate mortar, and heat treat it in a muffle furnace at 180°C for 5h to obtain the oxyhalide electrolyte material LiNbOCl4 powder.
[0050] Example 4
[0051] An oxyhalide electrolyte material, the preparation process of which is as follows:
[0052] In a glove box, weigh 0.8142g LiOH and 9.1858g NbCl5, mix with 200ml isopropanol in a beaker, and stir at room temperature until completely dissolved. Heat the solution to 80°C and continue stirring until the solution evaporates completely, leaving a gray solid at the bottom of the beaker. Scrape the solid from the bottom of the beaker, grind it in an agate mortar, and heat treat it in a muffle furnace at 120°C for 8h to obtain the oxyhalide electrolyte material LiNbOCl4 powder.
[0053] Example 5
[0054] An oxyhalide electrolyte material, the preparation process of which is as follows:
[0055] Weigh 0.6266g LiOH and 9.3733g TaCl5 in a glove box, mix with 200ml isopropanol in a beaker, and stir at room temperature until completely dissolved. Heat the solution to 80°C and continue stirring until the solution evaporates completely, leaving an off-white solid at the bottom of the beaker. Scrape the solid from the bottom of the beaker, grind it in an agate mortar, and heat treat it in a muffle furnace at 300°C for 8h to obtain the oxyhalide electrolyte material LiTaOCl4 powder.
[0056] Example 6
[0057] An oxyhalide electrolyte material, the preparation process of which is as follows:
[0058] In a glove box, weigh 0.6266g LiOH and 9.3733g TaCl5, mix with 200ml isopropanol in a beaker, and stir at room temperature until completely dissolved. Heat the solution to 80°C and continue stirring until the solution evaporates completely, leaving an off-white solid at the bottom of the beaker. Scrape the solid from the bottom of the beaker, grind it in an agate mortar, and heat treat it in a muffle furnace at 250°C for 8h to obtain the oxyhalide electrolyte material LiTaOCl4 powder.
[0059] Example 7
[0060] An oxyhalide electrolyte material, the preparation process of which is as follows:
[0061] Weigh 0.6266g LiOH and 9.3733g TaCl5 in a glove box, mix with 200ml isopropanol in a beaker, and stir at room temperature until completely dissolved. Heat the solution to 80°C and continue stirring until the solution evaporates completely, leaving an off-white solid at the bottom of the beaker. Scrape the solid from the bottom of the beaker, grind it in an agate mortar, and heat treat it in a muffle furnace at 280°C for 8h to obtain the oxyhalide electrolyte material LiTaOCl4 powder.
[0062] Example 8
[0063] An oxyhalide electrolyte material, the preparation process of which is as follows:
[0064] Weigh 0.6266g LiOH and 9.3733g TaCl5 in a glove box, mix with 200ml isopropanol in a beaker, and stir at room temperature until completely dissolved. Heat the solution to 80°C and continue stirring until the solution evaporates completely, leaving an off-white solid at the bottom of the beaker. Scrape the solid from the bottom of the beaker, grind it in an agate mortar, and heat treat it in a muffle furnace at 300°C for 10h to obtain the oxyhalide electrolyte material LiTaOCl4 powder.
[0065] Comparative Example 1
[0066] An oxyhalide electrolyte material, the preparation process of which is as follows:
[0067] In the glove box, 0.8142g LiOH and 9.1858g NbCl5 were weighed and placed in an agate mortar. The mixture was manually ground and mixed for 30 minutes. The mixed powder was transferred to a zirconia ball mill, 100g of 5mm zirconia grinding balls were added, a stainless steel sleeve was added and sealed, and then the glove box was taken out. The powder was ball milled at 500rpm for 48h using a planetary ball mill. The ball-milled powder was taken out of the glove box, placed in a box furnace, and heat treated at 120℃ for 5h to obtain the oxyhalide electrolyte material LiNbOCl4 powder.
[0068] Comparative Example 2
[0069] An oxyhalide electrolyte material, the preparation process of which is as follows:
[0070] In the glove box, 0.6266g LiOH and 9.3733g TaCl5 were weighed, put into an agate mortar, and manually ground and mixed for 30 minutes. The mixed powder was transferred to a zirconia ball mill, 100g of 5mm zirconia grinding balls were added, and a stainless steel sleeve was added and sealed. Then the glove box was taken out and ball milled at 500rpm using a planetary ball mill for 48h. The ball-milled powder was taken out of the glove box, put into a box furnace, and heat treated at 300℃ for 8h to obtain the oxyhalide electrolyte material LiTaOCl4 powder.
[0071] The performance of the positive electrode active materials provided in each embodiment and comparative example was tested, and the results are shown in the following table. The energy consumption and total preparation time of each embodiment and comparative example are shown in the following table.
[0072]
[0073]
[0074] As can be seen from the above table, the method provided in the embodiments of the present application can significantly improve the preparation energy consumption and preparation time compared to the solid phase method.
[0075] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0076] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b and c can be single or multiple.
[0077] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A liquid phase synthesis method of an oxychloride electrolyte material, characterized in that: The method comprises: Dissolving the reaction raw materials in a solvent to carry out a chemical reaction to obtain a product solution; Evaporating the product solution to obtain solid particles; The solid particles are heat treated to obtain an oxychloride electrolyte material Li x MO y Cl z , wherein M includes at least one of Sc, Y, Al, Ti, Zr, Hf, V, Nb and Ta, 1≤x / y≤4, 1≤z / y≤8; Wherein, the reaction raw materials include a lithium source and a M source, and the M source includes M chloride.
2. The liquid phase synthesis method of the oxychloride electrolyte material according to claim 1, characterized in that: The lithium source includes at least one of Li2O, LiOH and LiCl.
3. The liquid phase synthesis method of the oxychloride electrolyte material according to claim 1, characterized in that: The M source includes at least one of ScCl3, YCl3, AlCl3, TiCl4, ZrCl4, HfCl4, VCl5, NbCl5 and TaCl5.
4. The liquid phase synthesis method of the oxychloride electrolyte material according to claim 1, characterized in that: The solvent includes at least one of water, ethanol, isopropanol, methanol, n-butanol, acetone, methyl acetate, ethyl acetate, tetrachloroethylene, trichloroethylene and tetrahydrofuran.
5. The liquid phase synthesis method of the oxychloride electrolyte material according to claim 1, characterized in that: The mass ratio of the reaction raw material to the first solvent is 1:(8-1000).
6. The liquid phase synthesis method of the oxychloride electrolyte material according to claim 1, characterized in that: The evaporation temperature is 60° C. to 120° C., and the evaporation time is 4 h to 12 h.
7. The liquid phase synthesis method of oxychloride electrolyte material according to claim 1, characterized in that: The temperature of the heat treatment is 100° C. to 500° C., and the time of the heat treatment is less than or equal to 20 hours.
8. The liquid phase synthesis method of oxychloride electrolyte material according to claim 1, characterized in that: The method further includes mixing the solution with a hydrochloric acid solution to inhibit hydrolysis of the metal chloride.
9. The liquid phase synthesis method of the oxychloride electrolyte material according to claim 8, characterized in that: The volume concentration of hydrochloric acid in the hydrochloric acid solution is 30% to 36%.
10. The liquid phase synthesis method of oxychloride electrolyte material according to claim 8, characterized in that: The mass of the hydrochloric acid solution does not exceed 3% of the total mass of the reaction raw materials.
Citation Information
Patent Citations
Solid electrolyte material and battery using same
CN115428217A
Oxygen-containing chloride solid electrolyte and preparation method and application thereof
CN115842157A
Liquid-phase ultrasonic preparation method of solid electrolyte and obtained solid electrolyte
CN116588969A
Halide solid electrolyte and preparation method thereof
CN116960441A
Halide electrolyte material and preparation method thereof, solid-state battery and electric device
CN117728011A
Cited By
Niobium-based solid electrolyte and preparation method and application thereof
CN120199881A